Experimental study on dynamic characteristics of saturated remolded soft clay with sand particles - Wang, Sui; Cai, Yuanqiang; Zhang, Liyong; Pan, Yongjian; Chen, Bin; Zhao, Peng (Frontiers in Earth Science, 2023)
Long-term cyclic tests for different frequencies were carried out on remolded soft clay with different sand contents investigating how the frequency impacted the stress-strain, the dynamic shear modulus and the damping ratio of the remolded samples. Accordingly, when the sand content of the remolded specimen was 1.7%, the slope of the hysteresis curve of the remolded specimen tended to increase gradually with the increasing of frequency, and the hysteresis circle was slender and the area of the hysteresis circle tended to decrease gradually; when the sand content of the remolded specimen was 20%, the cumulative deformation of the specimen presented a gradual increase with the loading frequency, the slope of the hysteresis curve decreased gradually.The hysteresis curve shows a gradually decreasing slope, and the enclosed hysteresis circle area also tends to decrease. In addition, the higher the loading frequency, the stronger the deformation-resistant ability held by the specimen, mainly because the pore water pressure between soils' internal particles is not discharged in time, which makes the contact between the internal particles of the soil close, and the closer the structure of the soil, the smaller the compressive deformation of the soil, and the stabler of the soil.